2000
DOI: 10.1084/jem.192.12.1755
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylated Peptides Are Naturally Processed and Presented by Major Histocompatibility Complex Class I Molecules in Vivo

Abstract: Posttranslational modification of peptide antigens has been shown to alter the ability of T cells to recognize major histocompatibility complex (MHC) class I–restricted peptides. However, the existence and origin of naturally processed phosphorylated peptides presented by MHC class I molecules have not been explored. By using mass spectrometry, significant numbers of naturally processed phosphorylated peptides were detected in association with several human MHC class I molecules. In addition, CD8+ T cells coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
195
2

Year Published

2001
2001
2011
2011

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 194 publications
(204 citation statements)
references
References 49 publications
7
195
2
Order By: Relevance
“…CD8 ϩ T cells immunized to specifically recognize these phosphopeptides are also capable of recognizing intact human tumor cells, suggesting that phosphopeptides may represent a new class of targets for cancer immunotherapy (5,6). In these studies and others, T cell discrimination of the phosphopeptide versus its nonphosphorylated counterpart was observed, indicating that phosphorylation can influence peptide immunogenicity (5)(6)(7)(8)(9)(10)(11)(12)(13). Recent crystal structural definition of phosphorylated peptide-HLA-A2 complexes demonstrated direct and indirect interactions of the phosphoresidue with the MHC molecule, often significantly increasing the affinity of the phosphopeptide for MHC I. Additionally, phosphoresidues were solvent-exposed, suggesting the potential for direct interactions with the T cell receptor (14,15).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…CD8 ϩ T cells immunized to specifically recognize these phosphopeptides are also capable of recognizing intact human tumor cells, suggesting that phosphopeptides may represent a new class of targets for cancer immunotherapy (5,6). In these studies and others, T cell discrimination of the phosphopeptide versus its nonphosphorylated counterpart was observed, indicating that phosphorylation can influence peptide immunogenicity (5)(6)(7)(8)(9)(10)(11)(12)(13). Recent crystal structural definition of phosphorylated peptide-HLA-A2 complexes demonstrated direct and indirect interactions of the phosphoresidue with the MHC molecule, often significantly increasing the affinity of the phosphopeptide for MHC I. Additionally, phosphoresidues were solvent-exposed, suggesting the potential for direct interactions with the T cell receptor (14,15).…”
mentioning
confidence: 99%
“…Phosphorylation cascades are often dysregulated during malignant transformation, leading to uncontrolled proliferation, invasion of normal tissues, and distant metastasis (3,4). Limited but growing evidence has shown that tumor-associated phosphoproteins processed intracellularly through an endogenous pathway can give rise to phosphopeptides complexed to MHC I molecules, which are displayed on the cell surface (5,6). CD8 ϩ T cells immunized to specifically recognize these phosphopeptides are also capable of recognizing intact human tumor cells, suggesting that phosphopeptides may represent a new class of targets for cancer immunotherapy (5,6).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…If conversion of tyrosine to nitrotyrosine in autologous proteins can render these proteins recognizable as immunogenic autoantigens, this could have important implications for autoimmune diseases. Recent studies have indicated that a host of post-translational modifications, including glycosylation (19,20), phosphorylation (21,22), and cysteinylation (23,24), can all affect T cell immunoreactivity. Indeed, it has been proposed that these modifications may play a role in the initiation and/or maintenance of autoimmune disease by contributing to the breakdown of immunological tolerance (25,26).…”
mentioning
confidence: 99%
“…These epitopes would also be subjected to normal posttranslational processing, which has been shown to be important for presentation of some cysteinylated peptides, phosphopeptides, and glycopeptides to T cells. 22,23 Finally, because the protein continues to be expressed over time, transduced DCs may sustain epitope presentation longer than their peptide-pulsed counterparts.…”
Section: Cancer Gene Therapymentioning
confidence: 99%